ANALISIS KINERJA INDUSTRI USAHA KECIL DAN MENENGAH DENGAN MENGGUNAKAN RASIO RETURN ON ASSETS (ROA), DAN DEBT TO EQUITY RATIO (DER) DI KOTA MAKASSAR - Kurniati Karim (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of this research is to find out the influence of return on assets, debt to equity ratio and Performance of small and medium enterprises industry. The analysis technique has been done by using multiple linear regression analysis, F test and t test. The result of the research shows that ROA has influence to the Performance of small and medium enterprises industry the regression coefficient value is 1,421 and the t test significance value is 0,008. DER has does not have any influence to the Performance of small and medium enterprises industry the regression coefficient value is 0,153 and the t test significance value is 0,103